The content analysis of motion graphic elements in Malaysian music videos / Muhammad Shamie Khairulah ... [et al.] - Khairulah, Muhammad Shamie; Che Din, Sharkawi; Mohd Lazim, Nur Aniza; Mohamed Ghazali, Nabila Aimi (Universiti Teknologi MARA, Perak, 2023)
This research method examines how Malaysian music videos employ motion graphic components. The study's goal is to investigate the types and frequency of motion graphic elements utilized in Malaysian music videos, as well as how these elements relate to the video's visual appeal. The visual content of a total of 10 music videos by well-known Malaysian artists was examined by looking at the motion graphic elements which are elements of design, style, or types and principles of motion. The study's findings demonstrated that Malaysian music videos frequently incorporate motion graphic elements, with typography, animation, and visual effects being the most common forms. Additionally, the study discovered a substantial link between the employment of motion graphics and the videos' aesthetic design, indicating that motion graphics are a crucial component of visual storytelling in Malaysian music videos.